Analisis Kemampuan Masyarakat terhadap Laporan Hasil Studi Siswa dengan Menggunakan Rapor Online di SMP Negeri 12 Surabaya - Roekmini, Sri; Dwiyanti, Purwa (Jurnal Ilmiah FONEMA : Jurnal Edukasi Bahasa dan Sastra Indonesia, 2016)
The purpose of this study was determine the people’s satisfaction study reports of students using the online report card SMPN 12 Surabaya by permenpan no. 16 In 2014 the use of 8 (eigt) element of service brenhmarks. The method used is based on qualitative research descriptive. Data collectiob technique using data reduction, data presentation, and conclution. Result of researchon people’s satisfaction study report of studests using the online report is as follow: (1) Terms of opening the online report card is very easy; (2) steps in opening an online report card is very easy to understand; (3) opening the online report card does not necessarily sametimes fast and sometimes slow depending on signal its server; (4) fees charged opened an online raport card is quite cheap; (5) the ability of teachers (5) the ability of teachers clicking the entry value is less; (6) report card presented still more readble and comprehensible using the report printout rather than report card online; (7) competence implementing teacher to re entry is good value means the timely and many mistake; (8) complaints, suggestion and feedback if there are mistake biographical data such as respon from the school parent are very nice and friendly, direcly served